Lexical and Synthesis of Architectural Vernacularism of Lanting House in Banjarmasin - Mentayani, Ira; Aufa, Naimatul; Heldian, JC (Applied Engineering and Technology, 2022)
The cultural heritage of river life in Banjarmasin in the form of lanting houses is an important asset that can support the potential for the development of the city. One of the efforts to maintain and develop the existence of the lanting house can be done by tracing the lexicon and aspects of its vernacularism. From the historical and cultural studies of the origin of the lanting house, it was found that the culture of migrating (Lahei-Muara Teweh-Central Kalimantan) and trading culture (Hulu Sungai - South Kalimantan). To lead to a new development with new functions, the lexical "Rumah Lanting” and “Balanting” must be maintained. The word "lanting" and the process of "balanting" must be included such as gallery lanting, lanting guest house, or lanting homestay. Lexical "balanting" emphasis on lanting architecture which can only be docked and not settled. With the lexical "balanting" process, the architecture of the lanting house is floating and moves along the river. From analysis of 14 lanting houses located in the urban city, such as Kampung Seberang Masjid and on Bromo Island Kampung Mantuil, Banjarmasin City, it is found that the character of the lanting house which has spontaneous adaptive ability, multipurpose space expression, and flexibility of movement. The lanting house is able to move flexibly as well as the lexicon that is attached to it in the public perception towards artifact/notation of lanting. The influencing factor was the ethnolinguistic culture which influenced the journey of the Proto Banjar community-Dipa Daha people to the Banjar people during the Banjar Kingdom era. The result of the vernacularism synthesis confirms that the lanting house fulfills the rules as part of the vernacular architecture.